PEMBINAAN DIRI PTK-PNF BERWAJAH HUMANIS KOMUNIKATIF - Mulyana, Enceng (JIV-Jurnal Ilmiah Visi, 2008)
This article describes that self management preferably needs to be done by all human, including PTK PNF. The performance of humanistic and communicative behavior determines the success of professional tasks. The principles to be used are emotional control, active reaction, and refreshing and to confirm the learning process to be active, creative, effective, joyful, and also innovative.